(untitled) (Revista de Biología Marina y Oceanografía, 2022)
To test the island rule, the body size of P. mercatoris and P. aurata was measured, then statistical test and generalized linear models (GLM) were performed to explore changes in body length of both species. A smaller body length was evidenced in P. mercatoris supporting insular dwarfism. Additionally, P. mercatoris showed a trend of decreasing body size over time. This is the first report of the island rule in polyplacophorans. The temporal decrease in the size of P. mercatoris suggests a possible increase anthropogenic pressure, which should be studied to facilitate conservation and monitoring strategies.